Respect for farmer's methods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Issifou Tchan, from Benin, calls everyone to action: 'When, oh when, are people going to understand that we have to respect the local farmer's methods of cultivation ? Even now, there are some crops which have not moved on in terms of productivity...